Dynamic Bookstore Self-Ordering Kiosk System - ARUMUGAM NAIDU, JEVNITA; RAVI KUMAR, SAANUSHYAA; MUHAMAD SHAMBUDIN, UMMI NORAMIRAH; MASANDIG, HANNES (Multidisciplinary Applied Research and Innovation, 2024)
Kiosks are becoming increasingly popular in various industries because they allow customers to order for themselves and streamline business operations. This project explored the benefits of implementing kiosk systems in a bookstore to increase efficiency, improve the customer experience, and reduce operating costs. The goal of the kiosk system is to develop a self-order kiosk that allows customers to browse, purchase, and check out books without the assistance of an employee. The following materials were used to develop this project: Touch screen display, computer system, kiosk system application, inventory management system, payment processing system, and database management system. This project is targeted at all customers of Dynamic Bookstore for the system evaluation. The study used the waterfall model methodology to guide the development of this project. The implementation test result found that customers can search for items faster using a kiosk system. The online survey feedback study on customers found that 100% of respondents' perception of purchasing options shows that most customers prefer Dynamic Bookstores' self-ordering kiosk system. The results also indicate that efficiency,  ease of use,  time savings, and speed of browsing result in numerous customers using the kiosk system is noticeable. Future improvements include the implementation of popular mobile payment systems such as Apple Pay or Google Pay should be included to meet the increasing desire for digital payment methods and increase customer satisfaction. In summary, implementing a kiosk system in a large bookstore holds tremendous potential for improving the customer experience, simplifying operations, and achieving cost savings, according to the results of the project testing.